Combined Isolated Laugier’s Fracture and Distal Radial Fracture: Management and Literature Review on the Mechanism of Injury - Walid Osman; Meriem Braiki; Zeineb Alaya; Nader Naouar; Mohamed Ben Ayeche (Case Reports in Orthopedics)
Introduction. Isolated fracture of the trochlea is an uncommon condition requiring a particular mechanism of injury. Its association with a distal radial fracture is rare. We aimed through this case report to identify the injury mechanism and to assess surgical outcomes. Case Presentation. We report a 26-year-old female who was admitted to our department for elbow trauma following an accidental fall on her outstretched right hand with her elbow extended and supinated. On examination, the right elbow was swollen with tenderness over the anteromedial aspect of the distal humerus. The elbow range was restricted. Standard radiographs showed an intra-articular half-moon-shaped fragment lying proximal and anterior to the distal humerus. There was a comminuted articular fracture of the distal radius with an anterior displacement. A computed tomography revealed an isolated shear fracture of the trochlea without any associated lesion of the elbow. The patient was surgically managed. Anatomical reduction was achieved and the fracture was fixed with 2 Kirschner wires. The distal radial fracture was treated by open reduction and plate fixation. The postoperative course was uneventful with a good recovery. Conclusion. Knowledge of such entity would be useful to indicate the suitable surgical management and eventually to obtain good functional outcomes.